Summer Mesozooplankton Biomass Distribution in the West Spitsbergen Current (2001–2014) - Carstensen, Jacob; Olszewska, Anna; Kwasniewski, Slawomir (Frontiers in Marine Science, 2019)
Marine ecosystems in Arctic regions are expected to undergo large changes, driven by sea ice retreat and increasing influence of warmer and saline waters. We examined changes in the hydrography and mesozooplankton from a 14-year long time series in the West Spitsbergen Current during the summer period. The aim was to provide a contemporary description of spatial and temporal variations in the zooplankton community inhabiting the surface layer (0-60 m), over an area extending 6 latitudinal degrees and nearly 20 longitudinal degrees. A total of 296 samples were partitioned into three groups, based on salinity and temperature signatures, representing the western, eastern and coastal branches of the West Spitsbergen Current. Only the waters of the eastern branch, influenced by north-flowing Atlantic water, showed significant temporal trend in salinity, whereas no significant time trend was found for temperature in any of the three branches in the surface layer studied. Zooplankton biomass generally decreased from south to north in the western and eastern branches, suggesting poleward net loss of zooplankton, whereas relatively constant biomass in the coastal branch was likely sustained by higher production at the shelf break. The biomass remained constant over the study period for all three branches. Four species (Calanus finmarchicus, C. glacialis, C. hyperboreus, and Eukrohnia hamata) contributed almost 90% of the mesozooplankton biomass in all branches, with C. hyperboreus and C. glacialis being relatively important in the western and coastal branches, respectively. C. finmarchicus became increasingly important over time in the eastern branch, almost doubling its biomass and contributing more than 50% of the total biomass at the end of the study period. This increase was not associated with a general tendency towards more mature stages. C. finmarchicus copepodid CV and adults constituted >80 % of this species biomass in the western and eastern branches. In general, the relatively long time series, for Arctic standards, could not confirm expected drastic trends, but showed subtle changes over time overlaid by considerable interannual variability. Given the large inherent variability in zooplankton data, time series extending more than 14 years are needed for assessing trends in the West Spitsbergen Current.